MANAJEMEN DAN KEPEMIMPINAN - Nursyaidah, Nursyaidah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
The development of Islamic education such Islamic Boarding School is depending on how the management of the leadership is developed by the participant. This functions as planning, organizing, moving and supervising or control. A dicition maker plays domonantly in an organization. The role can affect morality, work satisfiction, safety, and quality of worklife and the lucky of the organisation